Pediatric sepsis definition - a systematic review protocol by the Pediatric Sepsis Definition Taskforce - Menon, K; Schlapbach, LJ; Akech, S; Argent, A; Chiotos, K; Chisti, MJ; Hamid, J; Ishimine, P; Kissoon, N; Lodha, R; Oliveira, CF; Peters, M; et al. (Lippincott, Williams & Wilkins, 2020)
Objectives: Sepsis is responsible for a substantial proportion of global childhood morbidity and mortality. However, evidence demonstrates major inaccuracies in the use of the term “sepsis” in clinical practice, coding, and research. Current and previous definitions of sepsis have been developed using expert consensus but the specific criteria used to identify children with sepsis have not been rigorously evaluated. Therefore, as part of the Society of Critical Care Medicine’s Pediatric Sepsis Definition Taskforce, we will conduct a systematic review to synthesize evidence on individual factors, clinical criteria, or illness severity scores that may be used to identify children with infection who have or are at high risk of developing sepsis-associated organ dysfunction and separately those factors, criteria, and scores that may be used to identify children with sepsis who are at high risk of progressing to multiple organ dysfunction or death. Data Sources: We will identify eligible studies by searching the following databases: MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials. Study Selection: We will include all randomized trials and cohort studies published between January 1, 2004, and March 16, 2020. Data Extraction: Data extraction will include information related to study characteristics, population characteristics, clinical criteria, and outcomes. Data Synthesis: We will calculate sensitivity and specificity of each criterion for predicting sepsis and conduct a meta-analysis if the data allow. We will also provide pooled estimates of overall hospital mortality. Conclusions: The potential risk factors, clinical criteria, and illness severity scores from this review which identify patients with infection who are at high risk of developing sepsis-associated organ dysfunction and/or progressing to multiple organ dysfunction or death will be used to inform the next steps of the Pediatric Sepsis Definition Taskforce.